Cancer gene therapy by viral and non-viral vectors - Brenner, Malcolm K., 1951-; Hung, Mien-chie (Hoboken, New Jersey : Wiley Blackwell, 2014)
"Translational medicine has opened the gateway to the era of personalized medicine. No longer a one-size-fits-all approach, the treatment of cancer is now based on an understanding of underlying biologic mechanisms and is increasingly being tailored to the molecular specificity of a tumor. Gene therapy in cancer has faced many technical barriers in the past but has recently shown significant progress that could allow stem cell and gene transfer therapies to make a major contribution to cancer therapy. The time appears ripe for a good, authoritative, book-length review of the state-of-the-art in this field. Gene Therapy by Viral and Non-viral Vectors provides a comprehensive overview of the pertinent molecular discoveries in the cancer field and explains the clinical ramifications and utility of these on gene-based cancer therapies. Designed as a volume in the book series Translational Oncology, edited by Robert Bast, Maurie Markman, and Ernest Hawk, this new book deals with the practice of gene therapy with reference to vectors for gene expression and gene transfer as well as viral therapy, and it will very nicely complement other books in the series, especially the volumes on immunotherapy and cell therapy. The content of the book also covers the history and current and future applications of gene transfer in cancer. This new volume provides expert insight on the current progress of viral and nonviral gene therapy with regard to delivery system, vector design, potential therapeutic genes, and principles and regulations for cancer gene therapy. It offers important and immediately applicable information to investigators, clinician-researchers, and medcial and graduate students with interest in this vital area of research"--Provided by publisher.
Machine generated contents note: ContributorsSeries ForewordPreface Part I: Delivery Systems 1. Translational Cancer Research: Gene Therapy by Viral and Non-viral Vectors Vincenzo Cerullo, Kilian Guse, Markus Vaha-Koskela and Akseli Hemminki 2. Retroviruses for Cancer Therapy Jiehua Zhou, Yue Ding, John Burnett and John Rossi 3. DNA Plasmids for Non-viral Gene Therapy of Cancer Amer N. Najjar, Judy S.E. Moyes and Laurence J.N. Cooper 4. Cancer Therapy with RNAi delivered by Nonviral Membrane/Core Nanoparticles Andrew B. Satterlee and Leaf Huang Part II: Targeted Expression 5. Cancer Gene Therapy by Tissue-specific and Cancer-targeting Promoters Jennifer L. Hsu, Longfei Huo, Chia-Wei Li, Yi-Hsin Hsu, Yan Wang and Mien-Chie Hung 6. MicroRNAs as Drugs and Drug Targets in Cancer Hui Ling and George A. Calin Part III: Principles of Clinical Trials in Gene Therapy 7. Regulatory Issues for Manufacturers of Viral Vectors and Vector-Transduced Cells for Phase I/II Trials Adrian P. Gee and Zhuyong Mei 8. U.S. Regulations Governing Clinical Trials in Gene Therapy Bambi Grilley 9. Remaining Obstacles to the Success of Cancer Gene Therapy Malcolm K. BrennerIndex.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Cancer -- Gene therapy; Genetic vectors -- Therapeutic use; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Neoplasms -- therapy; Genetic Therapy; Genetic Vectors -- therapeutic use; Oncolytic Virotherapy; Genetic Therapy; Gene therapy; Electronic books; Electronic books